LIBERATION AS A CAUSE AND EMPOWERMENT AS A HOPE TO GROWTH OF WOMEN IN EMILY’S JANE EYRE (International Journal of Food and Nutritional Sciences, 2022)
Fiction in general is based on real happenings or events. The dialogue, plot and characters are created out of the author’s imagination. It may be based on truth but it is not truth. In literature, it refers to novels and short stories. Let us explore the genre and enjoy reading classics of Jane Austen’s depiction of women in Sense and Sensibility and Pride and Prejudice.Sensibility is the nature of having the capacity to acknowledge and react to complex passionate or stylish impacts. It is the capacity to get sensations. It is likewise the investigation of writing that prompts a development of insight and sensitivity.Pride is a deep-down coordinated feeling that conveys two contradictory implications. With an antagonistic connotation pride alludes to a stupidly and irritation ally degenerate feeling of one's close to home estimation. With a positive connotation, pride alludes to unassuming and substance feeling of connection toward some's own particular decision and activities.Prejudice is a viable inclination towards a man or gathering part construct scarcely in light of their club enrollment. The word is regularly used to allude to as a rule "emotions towards individuals or a man.